2013
DOI: 10.1002/mrm.24843
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial perfusion quantification using theT1-based FAIR-ASL method: The influence of heart anatomy, cardiopulmonary blood flow and look-locker readout

Abstract: It is shown that the Look-Locker readout as well as the nonideal slice-selective inversion experiment have a considerable influence and have to be included properly to correctly quantify myocardial perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 67 publications
(137 reference statements)
0
12
0
Order By: Relevance
“…For the in vivo study, the T1GS and T1SS values used were the observed T1*s. As has been discussed previously , where the Deichmann‐Haase correction is used the ratio of the relaxation times remains constant T1GS/T1SS=T1*GS/T1*SS as the fitted values of A and B should remain the same for both the GS and SS cases. Thus, use of the correction would have no effect on the final value of MBF.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…For the in vivo study, the T1GS and T1SS values used were the observed T1*s. As has been discussed previously , where the Deichmann‐Haase correction is used the ratio of the relaxation times remains constant T1GS/T1SS=T1*GS/T1*SS as the fitted values of A and B should remain the same for both the GS and SS cases. Thus, use of the correction would have no effect on the final value of MBF.…”
Section: Methodsmentioning
confidence: 97%
“…where l ¼ 0.92 mL/g (25) is the blood-tissue partition coefficient of water, T blood 1 is the relaxation time of the blood pool and T GS 1 and T SS 1 are the values for the longitudinal relaxation time calculated for the myocardium, from the GS and SS experiment, respectively. For the in vivo study, the T GS 1 and T SS 1 values used were the observed T Ã 1 s. As has been discussed previously (26,27), where the Deichmann-Haase correction is used the ratio of the relaxation times remains constant…”
Section: Image Analysismentioning
confidence: 99%
“…At HF, the ASL sequence benefits from a better difference between T1 ns and T1 SS , this increases with the magnetic field strength for a given level of perfusion [159]. Over time, the ASL sequence has been properly applied to measure MBF in different mouse models of cardiovascular diseases, after some methodological adjustments to improve the resolution and scan time [2,32,55,80,135,144,162], with a proven reproducibility [32].…”
Section: Perfusionmentioning
confidence: 99%
“…This is in analogy to the "mean relaxation time approximation" in nuclear spin dephasing [38,62]. While considering the two high-frequency moments µ 0 and µ 1 , the corresponding (2,0)-GMA with f (2,0) = µ 0 and Ŵ (2,0) = µ 1 /µ 0 = 1/τ 0 describes the short time behavior of K(t) whereas the (0, 2)-GMA with the two low-frequency moments µ −2 and µ −1 and parameters f (0,2) = µ 2 −1 /µ −2 and Ŵ (0,2) = µ −1 /µ −2 = 1/τ −2 is a measure for the long time behavior.…”
Section: Appendices Appendix Amentioning
confidence: 95%